Kurdish Radio History of Broadcasting and Establishment 1939 -1945 - مەولود, محەمەد خدر (Sulaimani Journal for Humanities, 2019)
From November 1920, the anniversary of the establishment of the first radio station in the world, to 19-11-1939, the date of the broadcast of the Kurdish section of Radio Baghdad. From Cairo, the Kurdish media was the only read media. On November 19, 1939, the audio media became another part of the influence of the Kurdish media and gradually developed with the political and social situation of Kurdish society From the beginning of broadcasting and its uprising in Baghdad on Sunday 1-7-1939 until September 25, 1945 in Jaffa, Palestine, Kurdish listeners were broadcast outside Kurdistan Kurdish Radio has passed through many stages until it becomes an audible media with its own characteristics. In this research, the researcher discusses the importance of Kurdish radio and its establishment and emergence and considers it necessary to present a research on the establishment and development of Kurdish radio in a descriptive and historical manner It is important to develop the type of Kurdish radio stations and media.